Implementation of Enhance®Fitness: a scoping review using the RE-AIM framework. - Peng, Wenting; McKiddy, Sarah; Tomioka, Michiyo; Maruca, Dina L; Gell, Nancy M; Smith, Matthew L; Maloy, Caitlin; Belza, Basia (Gerontologist, 2026)
Background and Objectives Enhance®Fitness (EF) is an evidence-based group exercise program shown to promote physical and mental health among older adults. The scoping review aims to systematically map and synthesize the literature on EF using the RE-AIM framework (Reach, Effectiveness, Adoption, Implementation, and Maintenance). Research Design and Methods We conducted a scoping review of implementation studies focusing on EF or its predecessor, the Lifetime Fitness Program. Searches were conducted in 6 databases (PubMed, Embase, CINAHL, SCOPUS, Web of Science, and PsycINFO) and supplemented with EF-related publications listed on the program's official website. The search included all publications from January 1, 1980 through July 1, 2025. Results We included 33 publications. Reach showed EF primarily engaged community-dwelling older adults, typically female. Effectiveness outcomes were generally positive, including improved physical and mental health and reduced health care utilization. Adoption occurred across varied settings, supported by trained instructors and organizational alignment. Implementation typically followed the standard EF protocol of three 60-min sessions per week, delivered in person or remotely. Facilitators included instructor training, organizational support, and social engagement, while barriers included attendance challenges, resource needs, and technology issues. Maintenance was demonstrated through sustained program delivery across diverse community settings, and participant-level maintenance was reflected in follow-up assessments of health outcomes at common time points of 4, 6, or 12 months. Discussion and Implications EF is a widely adopted program with demonstrated benefits for older adults. Greater attention to equity and long-term sustainability is needed to strengthen future dissemination and support healthy aging.